2022
DOI: 10.51505/ijmshr.2022.6204
|View full text |Cite
|
Sign up to set email alerts
|

A Case of PCOS (Polycystic Ovarian Syndrome) Treated Successfully by the Application of Yoga Prana Vidya Healing System Through Sustained Selfpractice, Self-healing and Self-belief

Abstract: Introduction: Polycystic ovary syndrome (PCOS) is a disorder involving infrequent, irregular or prolonged menstrual periods, caused often by excess male hormone (androgen) levels. The ovaries develop numerous small collections of fluid — called follicles — and may fail to regularly release eggs. PCOS is a complex disorder of uncertain etiology, having strong evidence that it is a genetic disease. This paper presents a case of PCOS treated successfully by Yoga Prana Vidya healing protocols. Method: This report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…They can even be utilized to induce amenorrhea for lifestyle considerations [21]. A successful case of application of Yoga Prana Vidya protocols in the treatment and cure for PCOS [15] shows that persistent long-term healing treatments using YPV protocols with a disciplined lifestyle cured this condition successfully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can even be utilized to induce amenorrhea for lifestyle considerations [21]. A successful case of application of Yoga Prana Vidya protocols in the treatment and cure for PCOS [15] shows that persistent long-term healing treatments using YPV protocols with a disciplined lifestyle cured this condition successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Published literature shows there are more than 55 publications of research articles on successful applications of YPV healing to treat various illnesses. Published successful case reports include, treatment of difficult medical cases [3], diabetes management & control [4], removing arterial block in heart without surgery [5], vision improvements for participants of an Eye Camp [6], improvements in holistic wellbeing and immunity of participants in a one-month YPV intensive programme [7], Role of Yoga Prana Vidya in first aid and emergency [8], speedy recovery of COVID patients [9], treatment of hypothyroidism [10], Lowering academic anxiety and enhancing academic performance of high school children [11], saving life of a snake-bitten human female [12], managing the pain and side effects of a Hodgkin Lymphoma patient undergoing chemotherapy [13], healing treatment of a female patient suffering from kneecap dislocation [14],Treatment and cure of PCOS condition [15], a case of breast cancer successfully treated [16], De-addiction cases [17], etc.A review of published literature shows some experimental studies also conducted with successful outcomes such as improvements in the wellbeing of prisoners [18], significant reduction in anxiety and depression in corporate employees [19], improvements in the cognitive abilities and social behaviour of mentally challenged children [20]. This paper presents a case of a 22-year-old female from continental Europe, who was suffering from PCOS symptoms and hormonal shifts, availed distal YPV healing sessions online by joining a Healing camp organized by a group of healers based in India, with successful results.…”
Section: Hormonal Shifts and Pcos-like Symptomsmentioning
confidence: 99%
“…Literature shows published successful case reports on applications of YPV include, treatment of difficult medical cases, diabetes management and control, removing arterial block in heart without surgery, vision improvements for participants of an eye camp, improvements in holistic wellbeing and immunity of participants in a one-month YPV intensive programme, Role of YPV in first aid and emergency, speedy recovery of COVID patients, treatment of hypothyroidism, lowering academic anxiety and enhancing academic performance of high school children, saving life of a snake-bitten human female, managing the pain and side effects of a Hodgkin lymphoma patient undergoing chemotherapy, healing treatment of a female patient suffering from kneecap dislocation, treatment and cure of PCOS condition, a case of breast cancer successfully treated, de-addiction cases, etc. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] A review of published literature shows some experimental studies also conducted with successful outcomes such as improvements in the wellbeing of prisoners, significant reduction in anxiety and depression in corporate employees, and improvements in the cognitive abilities and social behaviour of mentally challenged children. [21][22][23]…”
Section: Yoga Prana Vidya System ®mentioning
confidence: 99%
“…It has been observed that Yoga Prana Vidya (YPV), which is a no-touch, no-drug bio-energy healing method has been used successfully to heal patients having simple to complex and multiple medical conditions. There are many recorded medical cases which show that YPV healing system has been successfully applied in management and control of various medical conditions, such as: Literature shows more than 45 research papers published in peer reviewed journals on the efficacy of YPV system protocols as complementary and also as an alternative mode of treatment, and some of these recent publications are cited in references [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Yoga Prana Vidya System (Ypv)mentioning
confidence: 99%